DECISION SUPPORT SYSTEM FOR SELECTING STUDY PROGRAMS FOR NEW STUDENTS AT STMIK SYAIKH ZAINUDDIN NW ANJANI USING THE PROFILE PATCHING METHOD - Wan Kamarul Zaman Haris Munandar; Lalu Puji Indra Kharisma; Ahmad Ashril Rizal; Asfal Fuad (JATISKOM : Jurnal Aplikasi Teknologi Informasi dan Sains Komputer, 2024)
The Decision Support System (DSS) is a computer-based information system that generates various alternative decisions to assist in addressing structured and unstructured problems. At STMIK Syaikh Zainuddin NW Anjani, the selection of study programs is still done manually, where prospective students are directly asked to choose which study program they wish to enter without any data processing based on their abilities and skills first. This approach can have negative consequences, as once they begin their studies in the chosen program, they may struggle to keep up due to misalignment with their skills, interests, and abilities, leading many to regret their choice and even decide to switch programs or transfer to another university; some may even attend less frequently. Therefore, there is a need for a system/application that can provide recommendations for study programs that align with their talents, interests, and capabilities. The Decision Support System for Selecting Study Programs for New Students at STMIK Syaikh Zainuddin NW Anjani uses the Profile Matching Method and the Prototype Method for software development, which begins with requirements gathering, prototype design, prototype evaluation, system coding, system testing, system evaluation, and system implementation. This decision support system calculates the exam scores taken by new students and successfully provides suitable recommendations based on their exam results. This application can also directly print the results of the calculations and recommendations for study programs for new students; they can also directly print the results of their tests.